آیات تورات میں رواداری کی تعلیمات:تجزیاتی مطالعہ: Teachings of Tolerance in the Verses of the Torah: An Analytical Study (Al-Aasar, 2025)
This research paper, Teachings of Tolerance in the Verses of the Torah: An Analytical Study, explores the moral and social principles of tolerance as reflected in the sacred text of the Torah. The study examines how the Torah, as a foundational divine scripture in the Abrahamic tradition, promotes compassion, justice, coexistence, and respect for humanity. Through a critical and comparative approach, the paper analyzes selected verses that emphasize forgiveness, love for one’s neighbor, protection of strangers, and peaceful coexistence among different communities. The research also investigates how these values influenced Jewish ethical thought and later contributed to broader interfaith moral frameworks. Furthermore, the study highlights that the Torah’s teachings on tolerance are not limited to historical or religious contexts but carry profound relevance for addressing modern issues such as racial discrimination, religious intolerance, and social polarization. By focusing on linguistic, contextual, and exegetical dimensions, the research aims to reveal the universal and timeless message of peace inherent in the Torah. Ultimately, this analytical study concludes that the Torah’s call for tolerance reflects the divine intention to build societies grounded in justice, mercy, and mutual understanding—principles that remain essential for global harmony in the contemporary world.